الليبرالية والديمقراطية في فكر جون رولز - ديب، ثائر (المركز العربي للأبحاث ودراسة السياسات, 2016)
This review of The Cambridge Companion to Rawls, concentrate on the liberalism and democracy in John Rawls thought. John Rawls is the most significant and influential philosopher and moral philosopher of the twentieth century. His work has profoundly shaped contemporary discussions of social, political and economic justice in philosophy, law, political science, economics and other social disciplines. In this book, many of the world is leading political and moral theorists discuss the full range of Rawls’s contribution to the concepts of political and economic justice, democracy, liberalism, constitutionalism, and international justice. There are also assessments of Rawls controversial relationships with feminism, utilitarianism and communitarianism.
تتركز هذه المراجعة لكتاب اتجاهات معاصرة في فلسفة العدالة: جون رولز نموذجا، وهو العنوان الذي اختارته الترجمة العربية لكتاب The Cambridge Companion to Rawls، على موضوعتي الليبرالية والديمقراطية في فكر جون رولز، وهو واحد من أبرز فلاسفة الأخلاق والسياسة في القرن العشرين، تركت أعماله أعمق الأثر في النقاشات المعاصرة حول العدالة الاجتماعية والسياسية والاقتصادية، سواء في الفلسفة أو القانون أو العلوم السياسية أو الاقتصاد، أو سوى ذلك من الفروع العلمية الاجتماعية. يضم الكتاب مجموعة لافتة من الدراسات، كتبها عدد من المنظرين الأخلاقيين والسياسيين العالميين البارزين، وناقشوا فيها مساهمات رولز المتعلقة بمفاهيم العدالة السياسية والاقتصادية، والديمقراطية، والليبرالية، والدستورية، علاوة على تقوييهم علاقات رولز التي هي محل جدال بكل من النسوية، والنفعية، والجماعوية.
Keywords: فلسفة العدالة -- الفلسفة السياسية -- الفلسفة الأخلاقية -- راولز، جون، ت. 2002 م; الليبرالية